An Error Analysis of Students’ English Vowel Pronunciation at The Sixth Semester of Islamic Studies of International Class Program of State Islamic Institute (IAIN) of Samarinda - Pitaloka, Anggi Diah (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2021)
Pronunciation is very important to avoid misunderstanding when people are communication. If it pronunciation is wrong, the meaning of the word changes. It can make someone not understand what we are saying. Many students still have error pronunciation. In IAIN Samarinda, Non-English studies are given English lessons like TOEFL, Public Speaking and language intensive. The lesson is not far from pronunciation, grammar, speaking, reading and listening. They are the students of International Class Program (KKI). The objective of research is to know is the students’ English vowel pronunciation error at the sixth semester of Islamic Studies of International Class Program of state Islamic institute (IAIN) of Samarinda. The research used descriptive qualitative. The main instrument is test. This research is carried out on the sixth semester students of International Class Program (KKI) of State Islamic Institute of Samarinda in the year 2019/2020. There are 15 students as participants. The result was found that there was an error in pronouncing English vowel. From the most common mistakes, to those that do not occur, are as follow: vowel /ʊə/ had 17 errors in both words, /ʌ/ occurred 15 errors, /ɒ/ occurred 12 errors, /ɑː/ occurred 8 errors, /ə/ occurred 7 errors, /ɪə/ occurred 6 errors, /ɔː/ occurred 4 errors, /eɪ/ occurred 4 errors, /ɔɪ/ occurred 4 errors, /ɛə/ occurred 4 errors, /aɪ/occurred 3 errors, /aʊ/ occurred 3 errors, /uː/ occurred 2 errors, /ɜː/ occurred 2 errors, /æ/ occurred 2 errors, /ɪ/ occurred 2 errors, /iː/ occurred 1 errors, /ʊ/ occurred 0 errors, /e/ occurred 0 errors, and /əʊ/ occurred 0 errors. The results showed that the participants were more dominant making mistakes in vowels /ʊə/, /ʌ/, and vowel /ɒ/.